ECOENZYME INHIBITORY TEST AGAINST STAPHYLOCOCCUS SP BACTERIAL GROWTH. ISOLATED FROM THE ECTODERMAL TISSUE OF DOG SKIN - Sinthalarosa, Margaretha Dhea; Suartha, I Nyoman; Sudipa, Putu Hendrywaesa (Buletin Veteriner Udayana; Vol. 15 No. 2 April 2023DO - 10.24843/bulvet.2023.v15.i02.p14, 2023)
Dogs are very susceptible to skin diseases such as dermatitis and bacteria that are often found in cases of dermatitis are Staphylococcus spp . Environmentally friendly herbal medicines and believed to be antimicrobial are ecoenzymes. The ecoenzymes in this study were made from papaya skin ( Carica papaya L.), soursop skin ( Annona muricata L.), neem leaf ( Azadirachta indica A. Juss) and lemongrass ( Cymbopogon winterianus Jowitt ). This study aims to determine the inhibitory power of ecoenzymes against Staphylococcus spp. bacteria isolated from dog skin ectodermal tissue. This research uses a quantitative method with modification of agar plate diffusion (Kirby Bauer) with well diffusion technique. This study was experimental and used a completely randomized design with 6 treatments, namely ecoenzyme concentrations of 30%, 50%, 70%, 100%, positive control and negative control. Data analysis used ANOVA and continued with the Games-Howell test. The results showed that the ecoenzyme used had inhibition against Staphylococcus spp. bacteria at concentrations of 50%, 70% and 100%.